A rare earth composite high-strength high-heat storage low-creep clay brick and preparation method thereof

By adopting the formulation and preparation process of rare earth composite high-strength, high heat storage and low creep clay bricks, the existing lattice bricks have been solved in terms of low high temperature strength, low life, and unstable creep rate, achieving the effects of high strength, high heat storage and low creep rate, improving overall stability and heat absorption and exothermic efficiency.

CN119751096APending Publication Date: 2025-04-04BAOTOU ANDESHANAI NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909243.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing lattice bricks have problems in high temperature strength, low life, unstable creep rate, etc., resulting in insufficient overall stability and heat absorption and release efficiency.

Method used

Rare earth composite high-strength, high heat storage and low creep clay bricks are used to prepare raw materials including kaolin, low-aluminum mullite, coke gemstone, high-aluminum bauxite clinker, soft clay, rare earth functional additives and lignin combined slurry, and prepared by water-soluble method, ball mill wet grinding, ball press press pressing and high-temperature sintering.

Benefits of technology

It improves the high temperature strength, heat storage and heat storage rate of clay bricks, reduces the creep rate and firing temperature, enhances thermal shock resistance and stability, and saves energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751096A_ABST
    Figure CN119751096A_ABST
Patent Text Reader

Abstract

The present invention provides a rare earth composite high-strength high-heat storage low creep clay brick and a preparation method thereof, and relates to the technical field of refractory bricks. The refractory bricks include the following raw materials by weight: 8-13 parts of 3-2mm kaolin, 6-10 parts of 2-1mm kaolin, 17-22 parts of 200-mesh kaolin, 16-20 parts of 3-1mm low-aluminum mullite, 22-25 parts of 0-1mm coke gemstone, 3-8 parts of 200-mesh high-aluminum bauxite clinker, 10-18 parts of soft clay, 1-10 parts of rare earth functional additives, and 4-7 parts of lignin-bound slurry; wherein the rare earth functional additive is a mixture of cerium oxide, lanthanum oxide and andalusite. The rare earth composite high-strength high-heat storage low creep clay brick prepared by the present invention has high heat storage and high heat storage rate, while broadening the application field of light rare earth products such as lanthanum and cerium, and providing a new market path for checker bricks for blast furnace hot blast stoves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory bricks, and particularly relates to a rare earth composite high-strength high-heat storage low-creep clay brick and a preparation method thereof. Background Art

[0002] As the core component of the hot blast stove, the regenerator is usually a vertically arranged tubular structure, a space filled with checker bricks. The flue gas from the combustion chamber flows downward to the regenerator where the heat storage body is stacked. The regenerator must not only have a fast heat transfer capability, but also must ensure a high temperature. The main function of the regenerator is to bear the force (structural stress and thermal stress) of the grid (or fire ball) on the heat storage body, maintain a suitable temperature environment for the heat storage body, and ensure the stability of the heat storage body's own structure. Because the temperature difference from top to bottom is very large, various materials need to be used during the construction process (basically the same as the checker brick material), and there are corresponding structures in the upper and lower directions to relieve internal stress, that is, a labyrinth connection device that can slide against each other during combustion.

[0003] The structure of the regenerator is mainly porous prismatic lattice bricks, or randomly stacked spherical fire-resistant balls. Different materials are selected according to the working temperature of the lattice bricks. The parts close to the combustion chamber have high temperatures, so materials with good high-temperature performance and anti-adhesion properties are selected, such as siliceous or low-creep high-aluminum materials. The parts close to the cold air can be selected with materials with good low-temperature performance and high strength, such as clay or andalusite clay. The intermediate materials have transitional properties, but high-temperature performance is still its primary requirement. In addition, sufficient expansion gaps should be left when stacking, so that each lattice brick can slow down the volume expansion caused by heating during the heating process, thereby avoiding additional thermal stress.

[0004] The main function of checker bricks is to store a certain amount of heat in a certain period of time, and to maintain a low creep rate. Low creep is a hard indicator requirement, because the hot blast furnace is all stacked with checker bricks, so there is a great demand for checker bricks in blast furnace hot blast furnaces. However, there are many problems with the current checker bricks in use. In recent years, patent documents have disclosed some formulas and data parameters, and there are some common problems, including: the shape and size of the checker bricks are used to improve the heat absorption and release capacity, but the material itself is not studied; low high temperature strength and low life; unstable creep rate and potential safety hazards; therefore, the overall stability and heat absorption and release efficiency are the focus that urgently needs to be improved. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a rare earth composite high-strength high-heat storage low-creep clay brick and a preparation method thereof to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the technical solution specifically adopted by the present invention is:

[0007] The first aspect of the present invention provides a rare earth composite high-strength, high-heat storage and low-creep clay brick, comprising the following raw materials in parts by weight: 8 to 13 parts of 3-2 mm kaolin, 6 to 10 parts of 2-1 mm kaolin, 17 to 22 parts of 200 mesh kaolin, 16 to 20 parts of 3-1 mm low-aluminum mullite, 22 to 25 parts of 0-1 mm pyrophosphate, 3 to 8 parts of 200 mesh high-aluminum bauxite clinker, 10 to 18 parts of soft clay, 1 to 10 parts of rare earth functional additives, and 4 to 7 parts of lignin binding slurry.

[0008] As a further illustration of the present invention, the rare earth functional additive is a mixture of cerium oxide, lanthanum oxide and andalusite.

[0009] As a further illustration of the present invention, the mass ratio of cerium oxide, lanthanum oxide and andalusite in the rare earth functional additive is 5.5-6.5:1.5-3.5:1-2.

[0010] As a further illustration of the present invention, the lignin-bound pulp is prepared by mixing calcium lignin sulfonate powder with water, and the Baume degree of the obtained lignin-bound pulp is 1.13.

[0011] The second aspect of the present invention provides a method for preparing the above-mentioned rare earth composite high-strength high-heat storage low-creep clay brick, comprising the following steps:

[0012] S1. Ingredients: kaolin, low-aluminum mullite, coke gemstone, high-aluminum bauxite clinker, soft clay and rare earth functional additives are weighed respectively according to the above weight ratio;

[0013] S2, obtaining lignin-bound slurry by a water-soluble method;

[0014] S3, raw material mixing: kaolin, low-aluminum mullite, pyrotechnics, high-aluminum bauxite clinker, soft clay, rare earth functional additives and lignin combined slurry are stirred and mixed to obtain a semi-dry mixture;

[0015] S4, pressing and molding: placing the semi-dry mixture obtained in step S3 in a brick press mold and pressing and molding to obtain a semi-finished refractory brick;

[0016] S5. Firing: The semi-finished refractory bricks are dried, sintered at high temperature and cooled in sequence to obtain finished rare earth composite high-strength, high-heat storage and low-creep clay bricks.

[0017] As a further illustration of the present invention, step S2 specifically comprises: stirring calcium lignin sulfonate powder in 45° C. water to obtain a lignin-bound slurry having a Baume degree of 1.13.

[0018] As a further illustration of the present invention, the raw material mixing process of step S3 specifically includes:

[0019] S301: Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 15-20 minutes;

[0020] S302: Mixing: Pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3-4 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2-3 minutes, then add the premixed powder and stir for 5-8 minutes. The total mixing time is 8-15 minutes to finally obtain a semi-dry mixture.

[0021] As a further illustration of the present invention, the preparation process of the rare earth functional additive powder comprises:

[0022] Cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 5.5-6.5:1.5-3.5:1-2, and the obtained mixture is ground by a ball mill wet grinding process for 8 hours to prepare a mixed material with a particle size D50<3 μm;

[0023] The obtained mixture is dried at a temperature of 110°C for 24 hours and then pressed into balls by a ball press at 10-20MPa;

[0024] The balled mixed material is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours;

[0025] The sintered mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled at D50<5μm to obtain rare earth functional additive powder.

[0026] As a further explanation of the present invention, step S4 is specifically:

[0027] The semi-dry mixture obtained in step S3 is weighed and poured into a brick press mold, and then flattened with a tool. A 630-ton screw brick press is used to press and shape the mixture. The pressure per unit area of ​​the mixture is controlled at 125-145 MPa to obtain a semi-finished refractory brick.

[0028] As a further explanation of the present invention, step S5 is specifically:

[0029] Drying the obtained semi-finished refractory brick at 80°C to 130°C for 24h to 36h to obtain a semi-finished brick blank, wherein the moisture content after drying is controlled to be ≤1%;

[0030] The semi-finished bricks are placed in a tunnel kiln and fired in a high temperature oxidizing atmosphere of 1360°C to 1400°C for 5h to 8h. They are cooled in the cooling section of the tunnel kiln and taken out to obtain finished rare earth composite high-strength, high-heat storage, low-creep clay bricks.

[0031] Compared with the prior art, the present invention has the following technical effects:

[0032] 1. The main raw materials are kaolin aggregate, coke, and high-alumina clinker, which are widely distributed and easy to obtain.

[0033] 2. The firing temperature is low during the preparation process, saving energy.

[0034] The rare earth composite high-strength, high-heat storage, low-creep clay brick prepared by the present invention has a firing temperature range of 1360°C to 1400°C. Rare earth oxides have certain fluxing and firing effects, which can reduce energy consumption and improve the physical indicators of clay refractory bricks. The firing temperature is about 30°C lower than that of traditional clay refractory bricks, which reduces the firing energy consumption in disguise.

[0035] 3. The rare earth composite high-strength, high-heat storage, low-creep clay bricks prepared by the present invention have high heat storage capacity and high heat storage rate, while broadening the application field of light rare earth products such as lanthanum and cerium, and providing a new market channel for checker bricks for blast furnace hot blast stoves. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention provides a flow chart of a method for preparing a rare earth composite high-strength high-heat storage low-creep clay brick. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Rare earth atoms have a compact electron layer structure, high electric charge, variable valence, large radius, strong polarization force, and active chemical properties. The inner 4f electrons of rare earth elements are shielded by the outer 5s and 5p electrons, which has a localization effect. The outermost electrons that determine the properties of the element are arranged in 4f and 5d to form a conduction band. The localization and incomplete filling of 4f electrons give rare earths unique optical, magnetic, and oxygen storage and release properties. 3+ Partially replace Al 3+etc. enter the crystal, and the binding force with the surrounding ions is enhanced, which promotes the enhancement of the stability of the organizational structure. The rare earth composite high-strength and high-heat storage clay brick provided by the present invention evenly disperses the high-emissivity material inside the refractory material or the matrix, thereby improving the heat storage efficiency of the clay brick. The present invention evenly distributes the high-emissivity fine powder material inside the refractory brick, and the contacted heat is covered from point to line and then to the surface, which improves the absorption rate and emissivity of the refractory brick to infrared radiation, promotes the full utilization of heat, saves thermal energy, and improves the thermal efficiency of the kiln. By adding rare earth functional additives, the present invention improves the thermal shock resistance, heat storage rate and unit heat storage of the finished product, and reduces the 0.2MPa creep rate and firing temperature.

[0039] The invention provides a rare earth composite high-strength high-heat storage low creep clay brick, which comprises the following raw materials in parts by weight: 8-13 parts of 3-2mm kaolin, 6-10 parts of 2-1mm kaolin, 17-22 parts of 200 mesh kaolin, 16-20 parts of 3-1mm low-aluminum mullite, 22-25 parts of 0-1mm pyrophosphate, 3-8 parts of 200 mesh high-aluminum bauxite clinker, 10-18 parts of soft clay, 1-10 parts of rare earth functional additives, and 4-7 parts of lignin binding slurry.

[0040] Specifically, the rare earth functional additive is a mixture of cerium oxide, lanthanum oxide and andalusite. The mass ratio of cerium oxide, lanthanum oxide and andalusite in the rare earth functional additive is 5.5-6.5:1.5-3.5:1-2.

[0041] Specifically, the lignin-bound pulp is prepared by mixing calcium lignin sulfonate powder with water, and the Baume degree of the obtained lignin-bound pulp is 1.13.

[0042] like Figure 1 As shown, the preparation method of the above-mentioned rare earth composite high-strength high-heat storage low-creep clay brick comprises the following steps:

[0043] S1. Ingredients: According to the above weight ratio, kaolin, low-aluminum mullite, coke stone, high-aluminum bauxite clinker, soft clay and rare earth functional additives are weighed respectively.

[0044] S2. Obtain lignin-bound slurry through a water-soluble method.

[0045] Step S2 specifically comprises: stirring the calcium lignin sulfonate powder in 45° C. water to obtain a lignin-bound slurry having a Baume degree of 1.13.

[0046] S3. Raw material mixing: kaolin, low-aluminum mullite, pyroxene, high-aluminum bauxite clinker, soft clay, rare earth functional additives and lignin combined slurry are stirred and mixed to obtain a semi-dry mixture.

[0047] The preparation process of the rare earth functional additive powder comprises: mixing cerium oxide, lanthanum oxide and andalusite in a mass ratio of 5.5-6.5:1.5-3.5:1-2, grinding the obtained ingredients by a ball mill wet grinding process for 8 hours to prepare a mixture with a particle size D50<3μm; drying the obtained mixture at a temperature of 110°C for 24 hours, and then pressing it into balls by a ball press under a condition of 10-20MPa; firing the balled mixture at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; crushing the fired mixed ball material into fine powder by a ball mill dry grinding process, and controlling the particle size to be D50<5μm, so as to obtain the rare earth functional additive powder.

[0048] The raw material mixing process of step S3 specifically includes:

[0049] S301: Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 15-20 minutes;

[0050] S302: Mixing: Pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3-4 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2-3 minutes, then add the premixed powder and stir for 5-8 minutes. The total mixing time is 8-15 minutes to finally obtain a semi-dry mixture.

[0051] S4, pressing and molding: placing the semi-dry mixture obtained in step S3 in a brick press mold and pressing and molding to obtain a semi-finished refractory brick.

[0052] Step S4 is specifically as follows: weigh the semi-dry mixture obtained in step S3 and pour it into the mold of a brick press, flatten it with a tool, and use a 630-ton screw brick press to press and shape it. The pressure per unit area of ​​the material is controlled at 125-145 MPa to obtain a semi-finished refractory brick.

[0053] S5. Firing: The semi-finished refractory bricks are dried, sintered at high temperature and cooled in sequence to obtain finished rare earth composite high-strength, high-heat storage and low-creep clay bricks.

[0054] Step S5 is specifically as follows: drying the obtained refractory brick semi-finished product at a temperature of 80°C to 130°C for 24h to 36h to obtain a semi-finished brick blank, and controlling the moisture content after drying to be ≤1%; placing the obtained semi-finished brick blank in a tunnel kiln, firing it in a high-temperature oxidizing atmosphere of 1360°C to 1400°C for 5h to 8h, cooling it along with the cooling section of the tunnel kiln, and taking it out to obtain a finished rare earth composite high-strength, high-heat storage, low-creep clay brick.

[0055] The following is explained in conjunction with specific embodiments:

[0056] The composition table of some raw materials used in the following examples and comparative examples

[0057]

[0058]

[0059] The following equipment information table of the examples and comparative examples is as follows:

[0060]

[0061] The GB / T31934-2015 test method was used to measure the heat storage rate and heat storage amount of the embodiments and comparative examples.

[0062] Embodiment 1:

[0063] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 10 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 7 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 6 parts of rare earth functional additives, and 5.5 parts of lignin-bound slurry.

[0064] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0065] S3. Preparation of rare earth functional additive powder: cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 5.5:3.5:1, and the obtained ingredients are ground by a ball mill wet grinding process for 8 hours to prepare a mixture with a particle size D50<3μm; the obtained mixture is dried at a temperature of 110°C for 24 hours, and then pressed into balls by a ball press under 10MPa; the balled mixture is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; the fired mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled to be D50<5μm, so as to obtain rare earth functional additive powder.

[0066] S4. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 15 minutes.

[0067] S5, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 5 minutes, and the total mixing time is 8 minutes.

[0068] S6. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 125MPa to obtain a semi-finished product.

[0069] S7, drying: the semi-finished product is dried at 80°C for 36 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0070] S8, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1360°C for 8 hours.

[0071] S9. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature. When taken out, rare earth composite high-strength, high-heat-storage, low-creep clay bricks are obtained.

[0072] The performance test of the rare earth composite high-strength, high-heat storage, low-creep clay brick obtained in Example 1 is as follows:

[0073] The heat storage rate is 273.35 J / min, and the saturated heat storage is 1396.43 J / g. Compared with the specific comparative example 1 of ordinary clay brick, the heat storage rate is increased by 13.4%, and the saturated heat storage is increased by 7.8%; the volume density is 2.41 g / cm 3 , room temperature compressive strength is 112Mpa, apparent porosity is 12.6%, and creep rate at 1280℃-50h is 0.133%.

[0074] Embodiment 2:

[0075] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 11 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 20 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 4 parts of 200 mesh high-aluminum bauxite clinker, 16 parts of soft clay, 4 parts of rare earth functional additives, and 6 parts of lignin-bound slurry.

[0076] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0077] S3. Preparation of rare earth functional additive powder: cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 6.5:2:1.5, and the obtained ingredients are ground by a ball mill wet grinding process for 8 hours to prepare a mixture with a particle size D50<3μm; the obtained mixture is dried at a temperature of 110°C for 24 hours, and then pressed into balls by a ball press under 13MPa; the balled mixture is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; the fired mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled to be D50<5μm, so as to obtain rare earth functional additive powder.

[0078] S4. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 18 minutes.

[0079] S5, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 6 minutes, and the total mixing time is 10 minutes.

[0080] S6. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 135MPa to obtain a semi-finished product.

[0081] S7, drying: the semi-finished product is dried at 100°C for 30 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0082] S8, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1370°C for 8 hours.

[0083] S9. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature. When taken out, rare earth composite high-strength, high-heat-storage, low-creep clay bricks are obtained.

[0084] The performance test of the rare earth composite high-strength, high-heat storage, low-creep clay brick obtained in Example 2 is as follows:

[0085] The heat storage rate is 266.58 J / min, and the saturated heat storage is 1369.57 J / g. Compared with the specific comparative example 1 of ordinary clay brick, the heat storage rate is increased by 11.2%, and the saturated heat storage is increased by 5.3%; the volume density is 2.35 g / cm 3 , room temperature compressive strength is 103Mpa, apparent porosity is 12.9%, and creep rate at 1280℃-50h is 0.142%.

[0086] Embodiment 3:

[0087] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 9 parts of 3-2mm kaolin, 9 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 18 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 6 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 8 parts of rare earth functional additives, and 6 parts of lignin-bound slurry.

[0088] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0089] S3. Preparation of rare earth functional additive powder: cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 6.5:1.5:2, and the obtained ingredients are ground by a ball mill wet grinding process for 8 hours to prepare a mixture with a particle size D50<3μm; the obtained mixture is dried at a temperature of 110°C for 24 hours, and then pressed into balls by a ball press under 20MPa; the balled mixture is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; the fired mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled to be D50<5μm, so as to obtain rare earth functional additive powder.

[0090] S4. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 20 minutes.

[0091] S5, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 4 minutes, add the lignin combined slurry obtained in step S2 and mix for another 3 minutes, then add the premixed powder and stir for 8 minutes, and the total mixing time is 15 minutes.

[0092] S6. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 145MPa to obtain a semi-finished product.

[0093] S7, drying: the semi-finished product is dried at 130°C for 24 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0094] S8, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1380°C for 8 hours.

[0095] S9. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature. When taken out, rare earth composite high-strength, high-heat-storage, low-creep clay bricks are obtained.

[0096] The performance test of the rare earth composite high-strength, high-heat storage, low-creep clay brick obtained in Example 3 is as follows:

[0097] The heat storage rate is 272.73 J / min, and the saturated heat storage is 1388.52 J / g. Compared with the specific comparative example 1 of ordinary clay brick, the heat storage rate is increased by 9.9%, and the saturated heat storage is increased by 2.5%; the volume density is 2.38 g / cm 3 , room temperature compressive strength 99Mpa, apparent porosity 12.9%, 1280℃-50h creep rate 0.139%.

[0098] Embodiment 4:

[0099] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 11 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 18 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 5 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 7 parts of rare earth functional additives, and 6 parts of lignin-bound slurry.

[0100] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0101] S3. Preparation of rare earth functional additive powder: cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 6:2:2, and the obtained ingredients are ground by a ball mill wet grinding process for 8 hours to prepare a mixture with a particle size D50<3μm; the obtained mixture is dried at a temperature of 110°C for 24 hours, and then pressed into balls by a ball press under 20MPa; the balled mixture is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; the fired mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled to be D50<5μm, so as to obtain rare earth functional additive powder.

[0102] S4. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 20 minutes.

[0103] S5, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 4 minutes, add the lignin combined slurry obtained in step S2 and mix for another 3 minutes, then add the premixed powder and stir for 8 minutes, and the total mixing time is 15 minutes.

[0104] S6. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 145MPa to obtain a semi-finished product.

[0105] S7, drying: the semi-finished product is dried at 130°C for 24 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0106] S8, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1380°C for 8 hours.

[0107] S9. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature. When taken out, rare earth composite high-strength, high-heat-storage, low-creep clay bricks are obtained.

[0108] The performance test of the rare earth composite high-strength, high-heat storage, low-creep clay brick obtained in Example 4 is as follows:

[0109] The heat storage rate is 265.38 J / min, and the saturated heat storage is 1370.13 J / g. Compared with the ordinary clay brick comparative example 1, the heat storage rate is increased by 10.8%, and the saturated heat storage is increased by 5.2%; the volume density is 2.37 g / cm 3 , room temperature compressive strength is 102Mpa, apparent porosity is 12.8%, and creep rate at 1280℃-50h is 0.158%.

[0110] Comparative Example 1:

[0111] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 10 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 7 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, and 5.5 parts of lignin-bound slurry.

[0112] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0113] S3. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker and soft clay powder for 15 minutes.

[0114] S4, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 5 minutes, and the total mixing time is 8 minutes.

[0115] S5. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 125MPa to obtain a semi-finished product.

[0116] S6. Drying: The semi-finished product is dried at 80°C for 36 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0117] S7, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1360°C for 8 hours.

[0118] S8. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature, and then taken out to obtain ordinary clay bricks.

[0119] The performance test of the ordinary clay brick obtained in Comparative Example 1 is as follows:

[0120] The heat storage rate is 236.72 J / min, the saturated heat storage is 1287.51 J / g, and the volume density is 2.38 g / cm 3 , room temperature compressive strength is 95Mpa, apparent porosity is 13.2%, and creep rate at 1280℃50h is 0.37%.

[0121] Comparative Example 2:

[0122] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 10 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 7 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 6 parts of cerium oxide powder, and 5.5 parts of lignin-bound slurry.

[0123] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0124] S3. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and cerium oxide powder for 15 minutes.

[0125] S4, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 5 minutes, and the total mixing time is 8 minutes.

[0126] S5. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 125MPa to obtain a semi-finished product.

[0127] S6. Drying: The semi-finished product is dried at 80°C for 36 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0128] S7, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1360°C for 8 hours.

[0129] S8. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature, and then taken out to obtain rare earth clay bricks.

[0130] The performance test of the rare earth clay brick obtained in Comparative Example 2 is as follows:

[0131] The heat storage rate is 252.64 J / min, the saturated heat storage is 1342.55 J / g, and the volume density is 2.39 g / cm 3 , room temperature compressive strength is 102Mpa, apparent porosity is 12.6%, and creep rate at 1280℃50h is 0.395%.

[0132] Comparative Example 3:

[0133] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 10 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyrophosphate, 7 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 6 parts of lanthanum oxide powder, and 5.5 parts of lignin-bound slurry.

[0134] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0135] S3. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and lanthanum oxide powder for 15 minutes.

[0136] S4, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 5 minutes, and the total mixing time is 8 minutes.

[0137] S5. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 125MPa to obtain a semi-finished product.

[0138] S6. Drying: The semi-finished product is dried at 80°C for 36 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0139] S7, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1360°C for 8 hours.

[0140] S8. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature, and then taken out to obtain rare earth clay bricks.

[0141] The performance test of the rare earth clay brick obtained in Comparative Example 3 is as follows:

[0142] The heat storage rate is 248.13 J / min, the saturated heat storage is 1325.96 J / g, and the volume density is 2.36 g / cm 3 , room temperature compressive strength is 97Mpa, apparent porosity is 12.7%, and creep rate at 1280℃50h is 0.431%.

[0143] Comparative Example 4:

[0144] S1. Ingredients: The ingredients are prepared according to the following raw materials in parts by weight: 10 parts of 3-2mm kaolin, 8 parts of 2-1mm kaolin, 19 parts of 200 mesh kaolin, 17 parts of 3-1mm low-aluminum mullite, 24 parts of 0-1mm pyroxene, 7 parts of 200 mesh high-aluminum bauxite clinker, 15 parts of soft clay, 6 parts of andalusite powder, and 5.5 parts of lignin-bound slurry.

[0145] S2. The calcium lignin sulfonate powder was stirred in 45° C. water by a water dissolution method to obtain a lignin-bound slurry (degree Baume 1.13° Bé).

[0146] S3. Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and andalusite powder for 15 minutes.

[0147] S4, mixing: pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2 minutes, then add the premixed powder and stir for 5 minutes, and the total mixing time is 8 minutes.

[0148] S5. Compression molding: Weigh the mixed semi-dry material, pour it into the brick press mold and flatten it with a tool, use a 630-ton screw brick press to press and mold it, and control the pressure per unit area of ​​the material at 125MPa to obtain a semi-finished product.

[0149] S6. Drying: The semi-finished product is dried at 80°C for 36 hours to obtain a semi-finished brick, and the moisture content after drying is controlled to be ≤1%.

[0150] S7, firing: firing the semi-finished bricks in a high temperature oxidizing atmosphere at 1360°C for 8 hours.

[0151] S8. Finished product: The fired refractory bricks are naturally cooled to room temperature as the furnace temperature, and then taken out to obtain ordinary clay bricks.

[0152] The performance test of the ordinary clay brick obtained in Comparative Example 4 is as follows:

[0153] The heat storage rate is 242.79 J / min, the saturated heat storage is 1301.83 J / g, and the volume density is 2.33 g / cm 3 , room temperature compressive strength 90Mpa, apparent porosity 13.1%, 1280℃50h creep rate 0.215%.

[0154] Comparing the performance test results of the clay brick obtained by adding the composite rare earth functional powder in Example 1 with the ordinary clay brick obtained in Comparative Example 1, it can be seen that the heat storage rate and the saturated heat storage capacity are significantly increased, the heat storage rate is increased by 13.4%, the saturated heat storage capacity is increased by 7.8%, and the creep rate of the important indicator is reduced from 0.37% to 0.133%. The performance test results of the clay bricks obtained by adding the composite rare earth functional powder in Example 1 were compared with the clay bricks obtained by adding a single rare earth oxide or andalusite powder in Comparative Examples 2, 3 and 4. It can be seen that the data after adding a single rare earth oxide or andalusite powder are obviously not as good as the data of the clay bricks added with the composite rare earth functional powder. The maximum heat storage rate and saturated heat storage capacity of adding a single substance can reach 6.3% and 4.1%, while the heat storage rate and saturated heat storage capacity of adding the composite rare earth material can reach 13.4% and 7.8%; the creep rate can reach 0.133% under the low creep standard when the composite rare earth material is added, while the creep rate of adding a single substance is 0.215-0.431%.

[0155] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0156] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A rare earth composite high-strength high-heat storage low-creep clay brick, characterized in that: The invention comprises the following raw materials in parts by weight: 8-13 parts of 3-2mm kaolin, 6-10 parts of 2-1mm kaolin, 17-22 parts of 200-mesh kaolin, 16-20 parts of 3-1mm low-aluminum mullite, 22-25 parts of 0-1mm pyrophosphate, 3-8 parts of 200-mesh high-aluminum bauxite clinker, 10-18 parts of soft clay, 1-10 parts of rare earth functional additive and 4-7 parts of lignin-bound slurry.

2. The rare earth composite high-strength high-heat storage low-creep clay brick according to claim 1 is characterized in that: The rare earth functional additive is a mixture of cerium oxide, lanthanum oxide and andalusite.

3. The rare earth composite high-strength high-heat storage low-creep clay brick according to claim 2 is characterized in that: The mass ratio of cerium oxide, lanthanum oxide and andalusite in the rare earth functional additive is 5.5-6.5:1.5-3.5:1-2.

4. The rare earth composite high-strength high-heat storage low-creep clay brick according to claim 1, characterized in that: The lignin-bound pulp is prepared by mixing calcium lignin sulfonate powder with water, and the Baume degree of the obtained lignin-bound pulp is 1.

13.

5. A method for preparing the rare earth composite high-strength, high-heat storage, low-creep clay brick according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Ingredients: kaolin, low-aluminum mullite, coke, high-aluminum bauxite clinker, soft clay and rare earth functional additives are weighed respectively according to the weight ratio described in any one of claims 1 to 4; S2, obtaining lignin-bound slurry by a water-soluble method; S3, raw material mixing: kaolin, low-aluminum mullite, coke gem, high-aluminum bauxite clinker, soft clay, rare earth functional additives and lignin combined slurry are stirred and mixed to obtain a semi-dry mixture; S4, pressing and molding: placing the semi-dry mixture obtained in step S3 in a brick press mold and pressing and molding to obtain a semi-finished refractory brick; S5. Firing: The semi-finished refractory bricks are dried, sintered at high temperature and cooled in sequence to obtain finished rare earth composite high-strength, high-heat storage and low-creep clay bricks.

6. The method for preparing the rare earth composite high-strength high-heat storage low-creep clay brick according to claim 5, characterized in that: Step S2 specifically comprises: stirring the calcium lignin sulfonate powder in 45° C. water to obtain a lignin-bound slurry having a Baume degree of 1.

13.

7. The method for preparing rare earth composite high-strength high-heat storage low creep clay brick according to claim 5, characterized in that: The raw material mixing process of step S3 specifically includes: S301: Premixing: Use a three-dimensional premixer to premix the prepared 200-mesh kaolin, 200-mesh high-alumina clinker, soft clay powder and rare earth functional additive powder for 15-20 minutes; S302: Mixing: Pour the prepared 3-2mm kaolin, 2-1mm kaolin, 3-1mm low-aluminum mullite, and 0-1mm pyrophosphate into a wet mill and stir for 3-4 minutes, add the lignin combined slurry obtained in step S2 and mix for another 2-3 minutes, then add the premixed powder and stir for 5-8 minutes. The total mixing time is 8-15 minutes to finally obtain a semi-dry mixture.

8. The method for preparing rare earth composite high-strength high-heat storage low creep clay brick according to claim 7, characterized in that: The preparation process of the rare earth functional additive powder comprises: Cerium oxide, lanthanum oxide and andalusite are mixed in a mass ratio of 5.5-6.5:1.5-3.5:1-2, and the obtained mixture is ground by a ball mill wet grinding process for 8 hours to prepare a mixed material with a particle size D50<3 μm; The obtained mixture is dried at a temperature of 110°C for 24 hours and then pressed into balls by a ball press at 10-20MPa; The balled mixed material is fired at a maximum firing temperature of 1500°C and a heat preservation time of 6 hours; The sintered mixed ball material is crushed into fine powder by a ball mill dry grinding process, and the particle size is controlled at D50<5μm to obtain rare earth functional additive powder.

9. The method for preparing rare earth composite high-strength high-heat storage low-creep clay brick according to claim 5, characterized in that: Step S4 is specifically as follows: The semi-dry mixture obtained in step S3 is weighed and poured into a brick press mold, and then flattened with a tool. A 630-ton screw brick press is used to press and shape the mixture. The pressure per unit area of ​​the mixture is controlled at 125-145 MPa to obtain a semi-finished refractory brick.

10. The method for preparing rare earth composite high-strength high-heat storage low creep clay brick according to claim 5, characterized in that: Step S5 is specifically as follows: Drying the obtained semi-finished refractory brick at 80°C to 130°C for 24h to 36h to obtain a semi-finished brick blank, wherein the moisture content after drying is controlled to be ≤1%; The semi-finished bricks are placed in a tunnel kiln and fired in a high temperature oxidizing atmosphere of 1360°C to 1400°C for 5h to 8h. They are cooled in the cooling section of the tunnel kiln and taken out to obtain finished rare earth composite high-strength, high-heat storage, low-creep clay bricks.